A new approach for university timetabling problems. (1st January 2014) - Badoni, Rakesh P.; Gupta, D.K.; Lenka, Anil K.
A general university timetabling problem formulated as a constraint satisfaction problem is solved by a new backtrack-free algorithm. This algorithm incrementally constructs a solution as is done by the usual backtracking algorithm. Whenever a dead-end is encountered, rather than backtracking to the previously assigned variable, it resolves its cause by using a local search min-conflicts-hill-climbing algorithm and then continues further progressively. The proposed algorithm is tested on a small dataset and its representative timetable is presented. It is also tested on a number of randomly generated university timetabling problems. The performance of the algorithm measured in terms of the number of iterations and the amount of CPU time in seconds required is compared with the backtracking algorithm and the min-conflicts-hill-climbing algorithm. It is observed that our algorithm takes less CPU time and less number of iterations.